Nilai-Nilai Yang Terdapat Dalam Film Animasi Lorong Waktu Episode 1-10 - Kurnia Ramadhanti Nurjannah; Mudzanatun; Fajar Cahyadi (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The background that drives this research is the decline in moral values ​​in elementary school age children. Through this, the Lorong Waktu animation is expected to be a reference for moral education in a fun way by watching to increase moral values ​​in elementary school age children. The focus of this research is to find the moral values ​​contained in the animated film Loong Waktu episodes 1-10. The aim of this research is to analyze the moral values ​​in the animated film Lorong Waktu episodes 1-10. Through this research, the researcher hopes to present the moral values ​​contained in the animated film Lorong Waktu episodes 1-10. This type of research is qualitative research. The use of qualitative methods in this study is to obtain in-depth data, data obtained from events that occur using several existing methods. The data in this study were obtained through interviews, documentation, as well as observation and recording methods. Based on the analysis of the animated film Lorong Waktu episodes 1-10 show that the film has moral values, namely respect, responsibility, honesty, justice, tolerance, wisdom, self-discipline, helpfulness, compassion, cooperation, courage and democracy. The twelve moral values ​​that are used as references are scattered and appear in every scene in the animated film Lorong Waktu Episodes 1-10.